The secret body : how the new science of the human body is changing the way we live - Davis, Daniel M. (Daniel Michael), 1970- (Princeton University Press, 2021)
"One of our most lauded scientist-writers shows how astonishing breakthroughs in medical science are changing previously immutable aspects of humanity. Welcome to a revolution in the science of human health. This book takes us to the frontier of medical research and reveals stunning recent advances that are changing our understanding of how human body works, how we combat and prevent disease and how we understand what it means to be human. We see how super-resolution nano-scopes are revealing hitherto hidden operations within our cells and opening up new new ways of manipulating the immune system; how human embryos can now be preserved alive long enough to see how genetic abnormalities can be corrected during the early stages of foetal development; how light is being used to excite pathways in the brain allowing us to understand and manipulate thoughts and feelings; how our rapidly increasing understanding of the microbiome is radically changing every aspect of human biology. These and many more astonishing discoveries are related as gripping dramas of discovery by an award-winning scientist at the very forefront of this adventure"--Publisher's description.